Croatian tourism and hospitality industry: Current state and future development perspectives - Slobodan Ivanovic; Ace Milenkovski; Vedran Milojica (UTMS Journal of Economics, 2015)
The economic crisis had a significant influence on the world economy, as well as on tourism and hospitality industry. Despite minor oscillations, European and world tourism turnover is registering a significant growth. Contemporary European tourists possess high purchasing power, as well as the tendency of undertaking travels, which is witnessed by the fact that Europe continues to be the leader in world tourism flows. As an EU member, Croatia needs to use this as a stimulation in further development of its tourism and hospitality industry. The purpose of the paper was to stress the importance of tourism development for the European and Croatian economy, while the goal of the paper was to present the state of European tourism and hospitality industry, to determine its positive trends, present the state of Croatian tourism and hospitality industry, and to propose future developmental guidelines in function of achieving competitive advantages.
Keywords: L83; 330; economic crisis; tourist turnover growth; Croatia; Europe; competitive advantages